Identifikasi Akhlak Mahmudah dalam Pendidikan Agama Islam (Kajian Kitab Hidayah al-Salikin) - Soleh, Warissuddin; Vahlepi, Sahrizal; Mustofa, Ady Muh. Zainul (MKWK PAI Universitas Jambi, 2024)
The purpose of Islamic education is to form a mahmudah morality. The formula for the moral provisions of mahmudah occupy an important position. There are many formulas about mahmudah morality which are narrative in nature and often overlap between one meaning and the other meaning. This study examines the identification of mahmudah morality in Islamic religious education through the study of the book Hidayah al-Salikin by Abdul Samad al-Falimbani. The focus of the research is the fifth chapter of the book. The research approach is qualitative with library research methods. Data analysis techniques using Miles and Huberman data analysis models. The results of the research are identified ten mahmudah morality which are very relevant to the formulation of the noble character education of Islamic religion. The Ten mahmudah morality described in the Book of Hidayah al-Salikin are: repentance, khauf, zuhud, be patient, thanksgiving, sincerity, tawakal, mahabbah, rida, and remembering death. Keyword: Moral identification; Mahmudah; Hidayah al-Salikin